Bioqualité Des Formes De Dissémination Des Protozoaires Flagellés Entériques Dans Les Eaux Souterraines (Sources Et Puits) En Zone Anthropisée (Yaoundé-Cameroun) - Ajeagah Gideon Aghaindum; Asi Quiggle Atud; Nola Moïse (European Scientific Journal, ESJ, 2016)
With an aim of characterizing the cysts of flagellated enteric protozoa present in groundwater of the town of Yaoundé, a descriptive and analytical study was carried out from February to July 2015 on the samples of 6 springs and 6 wells in 6 quarters of the city. The physico-chemical analysis proceeded at the same time on the field and at the laboratory. The observation of the cysts of the flagellated protozoa was done under the inverted microscope of mark Olympus CK2 to the objective 40X after concentration of the samples according to the method of sedimentation and the method of floating. The physicochemical analysis revealed slightly acid water (6, 04 ± 0, 49 U.C), average mineral-bearing (533, 70 ± 346, 18 µS/cm) and rich in suspended matter (14, 14 ± 11, 35 mg/L). The biological analyses revealed the presence of the cysts of the flagellated Protozoa with average densities of 162±115 cysts/L for Giardia intestinalis, 262 ± 280 cysts /L for Chilomastix mesnili, 89±101 cysts /L for Enteromonas hominis and 72 ± 80 cysts /L for Retortamonas intestinalis. In general, the greatest densities of cysts were recorded during the rainy season. The statistical tests revealed positive correlation between the cystic densities with MES, the color, turbidity and the organic matter (p < 0,05), and also negative correlation with nitrate (p < 0,05).This very high parasitological pollution makes water unfit for consumption. The use of untreated spring waters and wells could constitute a significant heath for the households living in the zone of study.